Estimates of Source Spectra of Ships from Long Term Recordings in the Baltic Sea - Karasalo, Ilkka; Östberg, Martin; Sigray, Peter; Jalkanen, Jukka-Pekka; Johansson, Lasse; Liefvendahl, Mattias; Bensow, Rickard (Frontiers in Marine Science, 2017)
Estimates of the noise source spectra of ships based on long term measurements in the Baltic sea are presented. The measurement data were obtained by a hydrophone deployed near a major shipping lane south of the Island Öland. Data from over 2000 close-by passages were recorded during a five month period from August to December 2014. For each passage, ship-to-hydrophone transmission loss (TL) spectra were computed by sound propagation modelling using 1. bathymetry data from the Baltic Sea Bathymetry Database (BSBD) 2. sound speed profiles from the HIROMB oceanographic model, 3. seabed parameters obtained by acoustic inversion of data from a calibrated source and 4. AIS data providing information on each ship's position. These TL spectra were then subtracted from the received noise spectra to estimate the free field source level (SL) spectra for each passage. The SL were compared to predictions by some existing models of noise emission from ships. Input parameters to the models, including e.g. ship length, width, speed, displacement and engine mass, were obtained from AIS data and the STEAM database of the Finnish Metereological Institute (FMI).